2021
DOI: 10.33158/asb.r143.v8.2022
|View full text |Cite
|
Sign up to set email alerts
|

Canonical interrelationships in morphological characters, yield and nutritional components of corn

Abstract: The increase in the world population, the need to increase food production, both in quantity and quality, becomes increasingly prominent. The objective of this work was to identify the canonical correlations between yield components, morphological characters, micronutrients, bioactive compounds and amino acids in corn. The experimental design used was a randomized block containing 11 treatments arranged in three replications. The treatments consisted of 11 Top Crosses hybrid genotypes, these being made through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Correa and Gonçalves, (2012), observed that the first two canonical variables explain more than 80% of the total variation contained in the original data set (97.94% of the accumulated total variance). Canonical correlations allow the realization of the correlation between groups of variables of interest (Carvalho et al, 2021). So agronomic and physiological characteristics were significant (P≤0.01, chi-square test) in the first and second canonical pairs, showing dependent relationships between the two groups of characteristics, with total correlations of these pairs of factors considered high (r = 0.99 and r = 0.90), respectively (Table 3).…”
Section: Figurementioning
confidence: 97%
“…Correa and Gonçalves, (2012), observed that the first two canonical variables explain more than 80% of the total variation contained in the original data set (97.94% of the accumulated total variance). Canonical correlations allow the realization of the correlation between groups of variables of interest (Carvalho et al, 2021). So agronomic and physiological characteristics were significant (P≤0.01, chi-square test) in the first and second canonical pairs, showing dependent relationships between the two groups of characteristics, with total correlations of these pairs of factors considered high (r = 0.99 and r = 0.90), respectively (Table 3).…”
Section: Figurementioning
confidence: 97%
“…Conventionally, breeders develop maize populations tolerant to abiotic stress through recurrent selection, and extract experimental cultivars or inbred lines to produce hybrids (Hallauer, Carena & Miranda, 2010;Carvalho et al, 2022). Recurrent selection, with the accumulation of favorable alleles, may be one of the main current and future strategies to increase the genetic base of genotypes and identify those with greater tolerance to abiotic stress (Das et al, 2021).…”
Section: Conventional Genetic Breedingmentioning
confidence: 99%
“…Grain yield has been the main character used to identify genotypes adapted to abiotic stress conditions (Ertiro et al, 2017;Ndlovu et al, 2022). However, due to the lower genetic contribution in the expression of this character, selection based on secondary characters has become efficient (Carvalho et al, 2022). Mainly for adaptation to environments with stress caused by meteorological variables, the interval between male and female flowering has been the main secondary character used (Lima et al, 2022;Zaidi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of these coefficients for traits of interest to genetic improvement facilitates identification of promising genotypes, where it becomes possible to use their results for indirect selection (Carvalho et al, 2015). Linear relationship studies are currently applied in soybean (Loro et al, 2021a), corn (Carvalho et al 2021), wheat (Loro et al, 2021b) andoat (Verdi et al, 2019), providing relevant information for indirect selection. However, there is still little information in this area, addressing the linseed crop.…”
Section: Agronomic Performance Of Linseed As a Function On Plant Arra...mentioning
confidence: 99%